2011
DOI: 10.1038/ng.762
|View full text |Cite
|
Sign up to set email alerts
|

A synonymous variant in IRGM alters a binding site for miR-196 and causes deregulation of IRGM-dependent xenophagy in Crohn's disease

Abstract: Susceptibility to Crohn's disease, a complex inflammatory disease, is influenced by common variants at many loci. The common exonic synonymous SNP (c.313C>T) in IRGM, found in strong linkage disequilibrium with a deletion polymorphism, has been classified as non-causative because of the absence of an alteration in the IRGM protein sequence or splice sites. Here we show that a family of microRNAs (miRNAs), miR-196, is overexpressed in the inflammatory intestinal epithelia of individuals with Crohn's disease and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
406
1
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 512 publications
(421 citation statements)
references
References 24 publications
5
406
1
4
Order By: Relevance
“…Apart from Atg16L1, other autophagy-related proteins such as IRGM [101][102][103] and NOD2 [104][105][106] are reported to be associated with Crohn's disease in humans [107]. However, since these proteins also play roles in biological processes other than autophagy, it remains unclear whether they relate to Crohn's disease via autophagy modulation.…”
Section: Crohn's Diseasementioning
confidence: 99%
“…Apart from Atg16L1, other autophagy-related proteins such as IRGM [101][102][103] and NOD2 [104][105][106] are reported to be associated with Crohn's disease in humans [107]. However, since these proteins also play roles in biological processes other than autophagy, it remains unclear whether they relate to Crohn's disease via autophagy modulation.…”
Section: Crohn's Diseasementioning
confidence: 99%
“…Nguyen and colleagues [129] found that only miR7 was downregulated in eight active colonic CD patients compared to six healthy controls. In addition, miR206, miR424 [121] , miR106b [130] and miR196 [131] are also upregulated in active colonic CD. However, is there any tissuespecific miRNA expression profile in the gastrointestinal tract?…”
Section: Mirnas In CDmentioning
confidence: 99%
“…It is generally believed that the mature miRNA then incorporates into the RNA-induced silencing complex, and guides this complex to the 3'-untranslated region (3'-UTR) of specific target mRNA transcripts to suppress translation or induce their degradation [1,2,[10][11][12][13] . However, miRNAbinding sites in coding regions as well as in the 5'-UTRs have also been reported [14][15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated miRNAs to be involved in inflammatory bowel disease (IBD) susceptibility, as polymorphisms in miRNA-binding sites affect the gene expression and thus seem to play a pivotal part in the pathogenesis of this chronic disorder [17,26] . Moreover, it has been found that miRNAs are differentially expressed in ulcerative colitis (UC) and Crohn's disease (CD) [27] , the two main forms of IBD.…”
Section: Introductionmentioning
confidence: 99%